The effects of adaptive directional microphone on auditory evoked cortical P300 response and speech performance in cochlear implant users - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2019)
Objective: The aim of this study was to evaluate the possible benefits of an adaptive directional microphone in noise by using auditory P300 and speech recognition scores (SRSs) in cochlear implant subjects. Design: The P300 and speech recognition scores were obtained (a) in quiet with an omnidirectional microphone (Quiet OM), (b) in noise with an omnidirectional microphone (Noise OM) and (c) in noise with an adaptive directional microphone (Noise BEAM) to compare the microphone effects. Study sample: Thirty-five cochlear implant subjects (22.87 +/- 1.30 years) Results: The latencies of the P2, N2 and P3 responses as the discrimination potentials were significantly prolonged in the Noise OM condition compared with those obtained in the Quiet OM and Noise BEAM conditions (p < 0.05). The latencies of all responses in the Quiet OM and Noise BEAM conditions were similarly obtained (p > 0.05). SRSs were significantly lower in the Noise OM condition than in the Quiet OM and Noise BEAM condition (p < 0.05). Conclusions: During noise, the adaptive directional microphone system provided a discrimination ability similar to that seen in quiet settings for cochlear implant users.
Keywords: Auditory P300; cochlear implants; noise; adaptive directional microphone; omnidirectional microphone; RECEPTION THRESHOLDS; MISMATCH NEGATIVITY; BACKGROUND-NOISE; BILATERAL USERS; PERCEPTION; POTENTIALS; INTELLIGIBILITY; RECOGNITION; RECIPIENTS; HEARING